Growth and Nitrate Uptake in Nannochloropsis gaditana and Tetraselmis chuii Cultures Grown in Sequential Batch Reactors - Rafay, Ramis; Uratani, Joao M.; Hernandez, Hector H.; Rodríguez, Jorge (Frontiers in Marine Science, 2020)
This study aims to determine the maximum specific biomass growth rates of Nannochloropsis gaditana and Tetraselmis chuii grown in sequential batch reactors. The maximum specific growth rates of N. gaditana and T. chuii were found to be 0.23 ± 0.04 gVSS/gVSS∙d and 0.22 ± 0.05 gVSS/gVSS∙d respectively. Optical density measured at 550 nm (OD550) accurately predict volatile suspended solids (VSS) concentration in N. gaditana growth media but not in T. chuii growth media. We observed decoupling of nitrate uptake from cell growth for both microalgae as growth continued well beyond the point where concentrations of nitrate in the growth media fell below the detection limit. This nitrate decoupling highlights the challenges in current microalgae growth models as growth was independent of the extracellular dissolved nitrogen in the system.